Catabolite Resistant Mutants of Bacillus subtilis - Sun, Dongxu (My University, 1984)
Mutations that confer resistance to catabolites in sporulation (crs) are located in six distinct loci on the chromosome of Bacillus subtilis. One of the crs mutations, crsEl, is found in the rpoBC operon which codes for β and β' subunits of RNA polymerase. Some stv and std mutations in the same operon also confer partial resistance to glucose. Another mutation, crsA47, is located in the gene for the σ-factor of RNA polymerase. These findings indicate that certain mutations in RNA polymerase can alter the response of cells to the inhibitory effect of catabolites on sporulation.
The crs mutants differ from each other in the growth characteristic and glucose utilization. Specific activities of IMP dehydrogenase and alkaline phosphatase vary widely among the crs mutants. These results suggest that the growth characteristic and the enzymes examined are not closely related to catabolite resistance in sporulation.
The crs mutants are resistant to at least one of the membrane-affecting agents, cerulenin, ethanol and NaCl in sporulation. This suggests that the membrane and its associated functions are important in initiation of sporulation. It is also suggested that functions affected in the crs mutants are related to the membrane.
Mutations scal9, rfmll, eryl and relA can offset the catabolite resistance in some of the crs mutants. Possibly, these suppressors suppress the catabolite resistance by affecting the membrane or by causing a metabolic imbalance which affect membrane functions.
Keywords: Biology; Biology